Diversity and indigenous uses of medicinal plants in the Buakhal area of the Garhwal Himalayan range, India. Issue 3 (2nd October 2021) - Kumari, Sharesth; Mehta, J. P.; Shafi, Snobar; Dhiman, Pooja; Krishan, Ram
ABSTRACT: The Indian Himalayan belt is renowned for its diverse topographic and climatic conditions, acts as home to many rare, endemic, and endangered ethnomedicinal plants. The present study aimed to document the medicinal plants and their indigenous uses in the Buakhal area of Pauri Garhwal (Uttarakhand, India) through personal interactions with local villagers. This study resulted in the documentation of 100 plant species of medicinal importance belonging to 87 genera and 45 families. Among these, seven species were trees, 17 shrubs, 71 herbs, and five climbers. Using the whole plant body (30% spp.) for the herbal preparations in the studied area, followed by the use of the leaves (28% spp.) and roots (21% spp.). Among the recorded plant species, Begonia picta, Berberis aristata, Bergenia ciliata, Centella asiatica, Dicliptera bupleuroides, and Malaxis acuminata were the medicinal plant species frequently extracted (from wild) by the villagers. The local floral diversity is used to treat gastrointestinal disorders, skin diseases, respiratory disorders, liver disorders, etc. However, important traditional knowledge and cultural practices are decreasing in the younger generation across the ethnic groups of the country due to modernization. The traditional knowledge and wisdom must be maintained and passed on to future generations.